Pyrolysis and spontaneous ignition of wood under transientirradiation: experiments and a-priori predictions - vermesi,I; Didomizio,M; richter,F; Weckman,E; Rein,G (Fire Safety Journal, 2017)
Wood is a material widely used in the built environment, but its flammability and response to fire are adisadvantage. Therefore, it is essential to have substantial knowledge of the behavior of wood undergoingexternal heating such as in a fire. The majority of studies in the literature use constant irradiation. Althoughthis assumption simplifies both modelling and experimental endeavors, it is important to assess the behaviorof materials under more comprehensive heating scenarios which might challenge the validity of solid-phaseignition criteria developed previously. These criteria are evaluated here for the spontaneous ignition undertransient irradiation by combining experimental measurements and a-priori predictions from a model of heattransfer and pyrolysis. We have applied a two-step transient irradiation in the cone calorimeter in the formof a growth curve followed by a threshold of constant irradiation. We used white spruce samples of size 100x 100 mm thickness of 38 mm measured the temperature at different depths and the mass loss. A one di-mensional model written in the open source code Gpyro is used to predict the pyrolysis behavior. The modelhas a chemical scheme in which the virgin components of wood (hemicellulose, cellulose, lignin) becomeactive, then decompose in two competing reactions: char and gas, and tar. The kinetic parameters, as wellas the thermal properties of the wood and char are taken from the literature, whileρand moisture contentare measured experimentally. A priori predictions of the temperature, made prior to the experiments, showexcellent agreement with the measurements, being within the experimental uncertainty range. The mass lossrate (MLR) predictions are qualitatively similar to the measurements, but there is a large uncertainty in themeasurements. For a-posteriori simulations, certain parameters are changed after having access to the mea-surements to improve the simulations. We found that the heat of reaction